2012
DOI: 10.1002/jms.3018
|View full text |Cite
|
Sign up to set email alerts
|

Using elemental profiles and stable isotopes to trace the origin of green coffee beans on the global market

Abstract: A broad elemental profile incorporating 54 elements (Li, Be, B, Na, Mg, Al, P, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Rb, Sr, Y, Mo, Pd, Ag, Cd, Sn, Sb, Te, Cs, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Er, Tm, Yb, Re, Ir, Pt, Au, Hg, Tl, Pb, Bi and U) in combination with δ(2) H, δ(13) C, δ(15) N and δ(18) O was used to characterise the composition of 62 green arabica (Coffea arabica) and robusta (Coffea canephora) coffee beans grown in South and Central America, Africa and Asia, the four most int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
8
38
0
Order By: Relevance
“…Africa 8 kg/ha) . The results are comparable with the range found by Santato et al . in coffee beans (+0.6‰ to 7.1‰).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Africa 8 kg/ha) . The results are comparable with the range found by Santato et al . in coffee beans (+0.6‰ to 7.1‰).…”
Section: Resultssupporting
confidence: 91%
“…). Similar variability ranges (from −29.4‰ to −25.3‰) were found in the study of Santato et al . for coffee beans cultivated in the same tropical areas.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies using isotopes as an indicator of coffee origin have focused primarily on the analysis of green coffee beans, although the vast majority of coffee sold to consumers is roasted. Santato et al reported δ 18 O values of bulk green coffee ranging from 19‰ to 37‰ and found generally lower values in Central America and higher values in Africa. Rodrigues et al reported δ 18 O values between 18.7‰ (from Papua New Guinea) and 34.8‰ (from Ethiopia).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have associated the chemical and isotopic characteristics of coffee with region of origin; previous approaches include measurements of carbon, nitrogen, boron, strontium, hydrogen, and oxygen stable isotope ratios, and elemental concentrations . These studies established that isotope ratios and elemental concentrations in coffee vary geospatially, and that coffees grown in the same region tend to have similar isotopic and elemental compositions . However, these approaches have been unable to predict spatial patterns in isotope ratios …”
Section: Introductionmentioning
confidence: 99%
“…Multiple elements including trace elements were also analyzed as potential parameters for distinguishing the origin of chicken samples since site-specific features can be provided (Franke et al, 2007;Furia, Naccarat, Sindona, Stabile, & Tagarelli, 2011;Pilgrim et al, 2010;Santato, Bertoldi, Perini, Camin, & Larcher, 2012). Meanwhile, the concentration of multiple elements is an indicator of the elemental composition of feed (Brunner, Katona, Stefánka, & Prohaska, 2010;Pisani, Protano, & Riccobono, 2008).…”
Section: Multi-element In Chicken Samples From Different Regionsmentioning
confidence: 99%